THE FORM AND MEANING OF USING SLANG IN THE COMMENT COLUMN OF THE TIKTOK ACCOUNT @FADILJAIDI - Yulia Friska Valentina Bakara; Tri Yuliawan (SOSIOEDUKASI, 2026)
This study aims to describe the form and meaning of the use of slang in the comment column of the Tiktok account @Fadiljaidi. This research uses a qualitative approach with a content analysis method. The research data is in the form of netizens' comments that contain slang on @Fadiljaidi's Tiktok account. Data collection is done through documentation techniques and note-taking techniques by taking screenshots of relevant comments. Data analysis uses the Miles and Huberman model which includes data collection, data reduction, data presentation, and conclusion drawn. The results of the study show that the use of slang in the comment column of the Tiktok account @Fadiljaidi consists of five forms, namely acronyms, abbreviations, contractions, clippings, and a variety of walikan. The acronym form was found as many as 10 data, abbreviations of 11 data, contraction of 8 data, clipping of 8 data, and a variety of guardians of 3 data. The slang used is generally formed through the process of shortening words, combining syllables, eliminating phonemes, and reversing the order of phonemes. In addition, the use of slang in the comment column has meanings related to the expression of feelings, familiarity, jokes, and social identities of social media users. This study concludes that slang on social media, especially Tiktok, develops dynamically following the creativity and communication needs of users in creating relaxed and intimate interactions.